The influence of moral judgment on physicians' prescription behaviour - Md Humayun Kabir, Sardar; Maulan, Suharni; Abd. Manaf, Noor Hazilah; Wan Nasir, Zaireena (Malaysian Public Health Physicians Association, 2021)
Pharmaceutical promotion towards physicians’ prescription behaviour is strongly interrelated. Identifying and addressing the ethical challenges in physicians’ prescription behaviour to increase the ethical predisposition of prescribing medicines is prioritized in global health and development plans. Hence, the importance of ethics in the professionalism of healthcare practitioners is now a growing concern. The main objective of this research is to investigate the influence of moral judgment on physicians' prescription behaviour. A survey has been conducted among 152 medical practitioners from private healthcare facilities in the metropolitan area of Kuala Lumpur and Selangor states of Malaysia. Principal component analysis method in EFA and structural equation modeling technique in CFA has been used to analyze the data and validate the model. The study found that physicians’ moral equity factor has a significant and positive influence on physicians’ prescription behaviour whereas their relativism and contractualism factors were not significant. The empirical evidence obtained from this study would make significant contributions to advancing the current knowledge of ethical prescription behaviour. Recommendations to physicians for more ethical prescription practices have been discussed at the end of this paper.